Financial Returns to Collecting Rare Political Economy Books - Heinrich Ursprung (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Rare books of political economy are eminently collectable. Using historical prices, I employ hedonic regressions to estimate financial returns to collecting the works of ten eminent political economists and develop a price index for this corpus of collectables. For the observation period 1975-2019, I find that in those 45 years investing in rare political economy books yielded an average annual real rate of return of 2.8%, which is well in line with the returns to collecting rare books of classical literature. Compared with other collectibles such as fine art, investing in rare books turns out to be financially more profitable.
Keywords: G11; Z11; 330; rare books; political economy; price indices; collectibles; cultural economics; history of economic thought